P119 An organoid platform for ovarian cancer captures intra- and interpatient heterogeneity. (1st November 2019) - Kopper, O; de Witte, CJ; Lõhmussaar, K; Espejo Valle-Inclan, J; Hami, N; Kester, L; Balgobind, AV; Korving, J; Proost, N; Begthel, H; van Wijk, LM; Revilla, SA; et al.
Abstract : Introduction/Background: Ovarian cancer (OC) is a heterogeneous disease usually diagnosed at a late stage. Experimental in vitro models that faithfully capture the hallmarks and tumour heterogeneity of OC are limited and hard to establish. Methodology: We present a protocol that enables efficient derivation and long-term expansion of OC organoids. Results: Utilizing this protocol, we have established 56 organoid lines from 32 patients, representing all main subtypes of OC. OC organoids recapitulate histological and genomic features of the pertinent lesion from which they were derived, illustrating intra- and interpatient heterogeneity, and can be genetically modified. We show that OC organoids can be used for drug-screening assays and capture different tumour subtype responses to the gold standard platinum-based chemotherapy, including acquisition of chemoresistance in recurrent disease. Finally, OC organoids can be xenografted, enabling in vivo drug-sensitivity assays. Conclusion: Taken together, this demonstrates their potential application for research and personalized medicine. Disclosure: No competing interests. Applicable funding sources: EIF | Stand Up To Cancer (SU2C) [Clevers, Kopper, Balgobind, Begthel] KWF Kankerbestrijding (Dutch Cancer Society) - UU2015-7743 [de Witte, van Roosmalen, Witteveen, Zweemer, Kloosterman] Gieskes Strijbis Foundation (1816199) [Clevers, Witteveen, Kloosterman, Zweemer, Lõhmussaar, Espejo Valle-Inclan, Hami, Bos, Snippert] Published in Nature Medicine. April 2019. dx.doi.org/10.1038/s41591-019-0422-6.